(untitled) (San Francisco, CA, 2009)
The world has changed dramatically since the best-selling The Organization of the Future was published in 1999. More than ever before, organizations and leaders need guidance for meeting the challenges of today's complex environment in order to thrive in the future. Filled with wisdom and insight on the most important issues facing organizations today, the twenty six chapters in The Organization of the Future 2 offer the wisdom of some of the most recognized thought leaders of our day. These experts share their unique vision of what the organization of the future should look like and what organizational leaders must do to survive in the tumultuous twenty-first century. The book describes how tomorrow's organizations can chart the path toward growth and prosperity in rapidly changing times and includes amazing examples of how organizations from different sectors have created cultures that are empowering their employees and transforming their industries and communities. The contributors offer varied and diverse views on the organization of the future—for entrepreneurs to large corporations, nonprofits, and universities—including three different yet complementary approaches to inclusion, integration, and horizontal organization. The final section of the book focuses on the leaders of the organizations of the future and shows how they can make a critical difference in the success of their enterprises.
Keywords: Organizational change,Organizational effectiveness,Industrial organization